Study of patients undergoing Endoscopic Retrograde Cholangiopancreatography (ERCP) at Tishreen University Hospital in Lattakia – Syria - Almostaffa, Osamah Omar; Zaizafoun, Hassan; Antonios, Milad (Journal of medical and pharmaceutical sciences, 2021)
Objective: The aim of this study is to evaluate the indications, findings, and complications of performing Endoscopic Retrograde Cholangiopancreatography (ERCP). Patients and Methods: A Prospective Observational Descriptive study conducted for the period from January 2020 to January 2021, 167 consecutive ERCP were performed at Tishreen University Hospital in Lattakia-Syria. Results: The median age was 58 years, 59.30% of patients were female. The most common indications for ERCP were common bile duct stones (44.9%) and obstructive jaundice (44.3%). The median number of attempts for cannulation was 2 counts, and 74.3% of the procedures were graded as with difficulty grade 1. The most common abnormal findings were common bile duct dilation (50.3%) and bile duct stones (43.7%). The most therapeutic endoscopic interventions were sphincterotomy (64.7%) and stone extraction balloons (68.9%). The therapeutic success rate was 93.5% with repeated the procedure and complications occurred in (10.8%) of patients. The most frequent complication was mild pancreatitis (6%). Death was reported in five cases (3%), one of them (0.6%) was due to ERCP. Conclusion: ERCP is a potential risk for complications, so physicians should be adept at recognizing and treating any complications as soon as they arise.